Аналітика великих даних: принципи, напрямки і задачі (огляд) - Балабанов, О.С. (Проблеми програмування, 2019)
Висвітлено основні напрямки, задачі та типи результатів глибокого аналізу великих (комп'ютеризованих) даних. Показано практичне значення великих даних та великої аналітики як фундаменту створення нових комп'ютерних технологій планування і керування у бізнесі. Виділено специфічні для великих даних режими використання даних (або роди завдань аналізу): «інтелектуальний» пошук потрібної інформації; масована переробка («відпрацювання») даних; індукція моделі об'єкту (середовища); екстракція знань з даних (відкриття структур і закономірностей). Окреслено етапи і організацію циклу робіт з аналізу даних. До типових класів задач великої аналітики належать: групування випадків (кластеризація); виведення цілевизначених моделей (класифікація, регресія, розпізнавання); виведення генеративних моделей; відкриття структур і закономірностей. Охарактеризовано особливості «глибокого навчання» та фактори його популярності. Виділено каузальні мережі як клас моделей, які поєднують у собі переваги генеративних, цілевизначених та багатоцільових моделей і відрізняються тим, що придатні для прогнозу ефектів керування (втручання). Вказано шість «опор», на яких будується методологічне ядро великої аналітики. Освещены основные направления, задачи и типы результатов анализа больших (компьютеризованных) данных. Показано практическое значение больших данных и большой аналитики как фундамента создания новых компьютерных технологий планирования и управления в бизнесе. Выделены специфичные для больших данных режимы использования данных (или роды заданий анализа): «интеллектуальный» поиск нужной информации; массированная переработка («отработка») данных; индукция модели объекта (среды); экстракция знаний из данных (открытие структур и закономерностей). Очерчено этапы и организацию цикла работ по анализу данных. К типовым классам задач большой аналитики относятся: группирование случаев (кластеризация); вывод целеопределенных моделей (классификация, регрессия, распознавание); вывод генеративных моделей; выявление структур і закономерностей. Охарактеризовано особенности «глубокого обучения» и факторы его популярности. Выделены каузальные сети как класс моделей, которые объединяют в себе преимущества генеративных, целеопределенных и многоцелевых моделей и отличаются тем, что пригодны для прогноза эффектов управления (вмешательства). Указано шесть «опор», на которых стоит методологическое ядро большой аналитики. We review directions (avenues) of Big Data analysis and their practical meaning as well as problems and tasks in this field. Big Data Analytics appears a dominant trend in development of modern information technologies for management and planning in business. A few examples of real applications of Big Data are briefly outlined. Analysis of Big Data is aimed to extract useful sense from raw data collection. Big Data and Big Analytics have evolved as computer society’s response to the challenges raised by rapid grows in data volumes, variety, heterogeneity, velocity and veracity. Big Data Analytics may be seen as today’s phase of researches and developments known under names ‘Data Mining’, ‘Knowledge Discovery in Data’, ‘intelligent data analysis’ etc. We suggest that there exist three modes of large-scale usage of Big Data: 1) ‘intelligent information retrieval; 2) massive “intermediate” data processing (concentration, mining), which may be performed during one or two scanning; 3) model inference from data; 4) knowledge discovery in data. Stages in data analysis cycle are outlined. Because of Big Data are raw, distributed, unstructured, heterogeneous and disaggregated (vertically splitted), this data should be prepared for deep analysis. Data preparation may comprise such jobs as data retrieval, access, filtering, cleaning, aggregation, integration, dimensionality reduction, reformatting etc. There are several classes of typical data analysis problems (tasks), including: cases grouping (clustering), predictive model inference (regression, classification, recognition etc.), generative model inference, extracting structures and regularities from data. Distinction between model inference and knowledge discovery is elucidated. We give some suggestion why ‘deep learning’ (one of the most attractive topic by now) is so successive and popular. One of drawbacks of traditional models is they disability to make prediction under incomplete list of predictors (when some predictors are missed) or under augmented list of predictors. One may overcome this drawback using causal model. Causal networks are illuminated in the survey as attractive in that they appear to be expressive generative models and (simultaneously) predictive models in strict sense. This means they pretend to explain how the object at hand is acting (provided they are adequate). Being adequate, causal network facilitates predicting causal effect of local intervention on the object.